Water Quality Evaluation of Central Lombok Awang Bay Using Zooplankton Diversity as a Bioindicator - Sagista, Reza; Leksono, Amin Setyo; Retnaningdyah, Catur (Biotropika: Journal of Tropical Biology, 2024)
The water quality in Awang Bay, West Nusa Tenggara, Indonesia, is considered to be polluted due to human activities. This research aims to evaluate the water quality in Teluk Awang based on the physicochemical properties of water and zooplankton as bioindicators. Sampling was conducted at three beach locations: Awang, Ujung Kelor, and Ekas. The physicochemical water quality parameters measured included water temperature, pH, dissolved oxygen (DO), salinity, and transparency. Additionally, environmental factors were observed based on the naturalness and hemeroby index. The result of the identification and counting of the abundance of each zooplankton can then be used to analyze including taxa richness, total density, the diversity index of Shannon-Wiener (HSW), Margalef diversity index, Simpson diversity index, evenness index (E), and dominance index (C). The resulting research indicated that the physicochemical water qualities have met government quality standards for marine biota needs, except for the level of transparency at Ekas Station 3. Ekas Beach has the highest level of transparency, diversity, taxa richness, and total abundance of zooplankton, indicating the best water quality. Ujung Kelor Beach, which has the highest level of naturalness and the highest DO concentration, has moderate zooplankton diversity, indicating that the water quality is in the medium category. Meanwhile, Awang Beach, which had the highest human activity and the worst water quality, was characterized by low levels of transparency and DO, low diversity, taxa richness, and an abundance of zooplankton. Therefore, diversity, taxa richness, and abundance of zooplankton can be used as a bioindicator for changes in water quality.